Effects of eddy currents on selective spectral editing experiments at 3T. Issue 3 (22nd July 2017) - Oeltzschner, Georg; Snoussi, Karim; Puts, Nicolaas A.; Mikkelsen, Mark; Harris, Ashley D.; Pradhan, Subechhya; Tsapkini, Kyrana; Schär, Michael; Barker, Peter B.; Edden, Richard A.E.
Abstract : Purpose: To investigate frequency‐offset effects in edited magnetic resonance spectroscopy (MRS) experiments arising from B0 eddy currents. Materials and Methods: Macromolecule‐suppressed (MM‐suppressed) γ‐aminobutyric acid (GABA)‐edited experiments were performed at 3T. Saturation‐offset series of MEGA‐PRESS experiments were performed in phantoms, in order to investigate different aspects of the relationship between the effective editing frequencies and eddy currents associated with gradient pulses in the sequence. Difference integrals were quantified for each series, and the offset dependence of the integrals was analyzed to quantify the difference in frequency (Δf) between the actual vs. nominal expected saturation frequency. Results: Saturation‐offset N‐acetyl‐aspartate‐phantom experiments show that Δf varied with voxel orientation, ranging from 10.4 Hz (unrotated) to 6.4 Hz (45° rotation about the caudal–cranial axis) and 0.4 Hz (45° rotation about left–right axis), indicating that gradient‐related B0 eddy currents vary with crusher‐gradient orientation. Fixing the crusher‐gradient coordinate‐frame substantially reduced the orientation dependence of Δf (to ∼2 Hz). Water‐suppression crusher gradients also introduced a frequency offset, with Δf = 0.6 Hz ("excitation" water suppression), compared to 10.2 Hz (no water suppression). In vivo spectra showed a negative edited "GABA" signal, suggesting Δf on the order of 10 Hz; with fixed crusher‐gradient coordinate‐frame, the expected positive edited "GABA" signal was observed. Conclusion: Eddy currents associated with pulsed field gradients may have a considerable impact on highly frequency‐selective spectral‐editing experiments, such as MM‐suppressed GABA editing at 3T. Careful selection of crusher gradient orientation may ameliorate these effects. Level of Evidence : 2 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2018;47:673–681.